Stein and Nagatani on Stabilization Policies in a Growing Economy - Mackay, R. J. (Review of Economic Studies, 1973)
Journal Article Stein and Nagatani on Stabilization Policies in a Growing Economy Get access Robert J. Mackay Robert J. Mackay Virginia Polytechnic Institute and State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 4, October 1973, Pages 571–578, https://doi.org/10.2307/2296590 Published: 01 October 1973